Discussion of Improving Bankruptcy Procedure by Philippe Aghion, Oliver Hart, and John Moore - Philip H. Dybvig (Washington University Law Quarterly, 1994)
By bringing together a wide range of bankruptcy scholars and practitioners, this Conference has made very clear the broad extent of opinions about current bankruptcy law. One extreme view suggests bankruptcy is a mysterious and wonderful process that has many benefits that are difficult or impossible to quantify or enumerate. A polar extreme view, presented in the paper I am discussing by Aghion, Hart, and Moore (AHM), is that bankruptcy is a complicated and costly solution to a very simple problem. I suspect the truth (or at least the most useful view of the world) lies between the two extremes. It certainly should be possible to quantify and enumerate the functions of the bankruptcy process, and the resulting demystification should be an input to improved policy decisions. On the other side, the existing proposed simple alternatives to bankruptcy, such as that of AHM, neglect important functions of bankruptcy. The AHM paper in particular weakens its own case by neglecting existing institutions. Perhaps because of our shared economic training, I am predisposed to be sympathetic with the central motivation of AHM. For example, I have a casual perception that Chapter 11 works poorly for large firms. Based on what I know about large publicized bankruptcies, the bankruptcy process is unnecessarily slow, arbitrary, manipulable, and destructive of prior contracting. Unfortunately, the hard evidence I am aware of neither confirms nor refutes my perception To the extent that my perception is accurate, each of the shortcomings of the bankruptcy process causes avoidable economic damage, the cost of which must be borne by somebody and is a dead-weight loss to society as a whole.
Keywords: Bankruptcy law; International; Oliver Hart; Bankruptcy reorganization; Bankruptcy; Law & economics